2017
DOI: 10.1186/s13075-016-1201-0
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin (S100A8/A9) has the strongest association with ultrasound-detected synovitis and predicts response to biologic treatment: results from a longitudinal study of patients with established rheumatoid arthritis

Abstract: BackgroundCalprotectin (S100A8/A9 or MRP8/14) and S100A12 (leukocyte-derived proteins), interleukin 6 (IL-6) and vascular endothelial growth factor (VEGF) are markers of inflammation and angiogenesis. Ultrasound (US) is sensitive for detection of greyscale synovitis and power Doppler (PD) vascularization. The objective of the present study was to explore the associations between calprotectin, S100A12, IL-6, VEGF, erythrocyte sedimentation rate, C-reactive protein and a comprehensive US assessment in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The response of calprotectin to bacterial respiratory infections is well in line with previous reports demonstrating increase in calprotectin in sepsis [17][18][19][20] as well as other inflammatory conditions with neutrophil activation such as appendicitis, synovitis and prosthetic joint infections [21][22][23] .…”
Section: Type Of Infectionsupporting
confidence: 87%
“…The response of calprotectin to bacterial respiratory infections is well in line with previous reports demonstrating increase in calprotectin in sepsis [17][18][19][20] as well as other inflammatory conditions with neutrophil activation such as appendicitis, synovitis and prosthetic joint infections [21][22][23] .…”
Section: Type Of Infectionsupporting
confidence: 87%
“…GS score is generally used for synovitis evaluation and PD score is for vascularization evaluation in the joints of RA. [52] Studies demonstrated a correlation between CLP levels and US sum scores, GS and PD synovitis scores. [7,52] Additionally, Hurnakova et al [53] analyzed the value of serum CLP levels for PD synovitis in RA by a multivariate regression analysis.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2019 / mentioning
confidence: 98%
“…The noteworthy association between serum CLP and swollen joint count (SJC), tender joint count (TJC) was observed in several studies. [3,7,52,53] CLP circulatory levels have significant correlations with grip strength (r = -0.22, P < 0.05) and circumferences of proximal interphalangeal (PIP) joints (r = 0.33, P < 0.05) in a cross-sectional study of 70 RA patients. [4] Above studies also suggested an association of serum CLP and other serological indicators.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2019 / mentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) is an important pro-inflammatory factor that has a role in the pathogenesis of RA, and is also the most important and most powerful known pro-angiogenic factor [11,12]. Rheumatologists have examined the role of VEGF in the angiogenesis of RA, and the effect of inhibition of VEGF as a potential therapy for RA.…”
Section: Introductionmentioning
confidence: 99%